Pengaruh Size dan Sales Growth terhadap Nilai Perusahaan Sektor Kesehatan yang Go Public di Indonesia - Rismayani; Azhar Latief; Yulia Tri Kusumawati (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to test and analyze how company size calculated based on total assets and sales growth rate calculated by sales growth rate affect company value as measured by Tobin's Q method. The data used in this study is secondary data from the financial statements of companies in the health sector taken from the official website of the Indonesia Stock Exchange. The sample of this study consisted of 30 companies in the health sector for 2020-2022, and 60 companies in the health sector selected using purposive sampling method. The data collection technique applied in this research is the documentation technique. The data analysis approach applied in this study is multiple regression analysis. The results state that company size (size) has a partially insignificant effect on firm value, and the level of sales growth has a partially insignificant effect on firm value. While simultaneously, company size and sales growth rate have no significant effect on firm value.